Inovasi Pengolahan Sampah Organik Terpadu Melalui Budidaya Maggot di Pondok Pesantren Daarul Hidayah Pandaan - Hasyim, Muhammad Asmuni; Mukmin, Muhammad Islahul; Fitriyah, Fitriyah Fitriyah (JRCE (Journal of Research on Community Engagement), 2024)
Pasuruan Regency is one of the regions in East Java which has a lot of potential in the industrial, trade, education, economic, tourism, and agricultural sectors, besides that, Pasuruan Regency is also famous for its many Islamic boarding schools. One of the Islamic boarding schools that is in the process of pioneering and developing is the Darul Hidayah Islamic Boarding School in Tawangrejo Village, Pandaan District, Pasuruan Regency. In addition to studying religious knowledge, students in Islamic boarding schools are also trained for other activities, including entrepreneurship programs, through several activities including cultivating herbal plants, fishing, and animal husbandry. One of the problems in the Islamic boarding school development process is waste processing which cannot be done in an integrated manner. This community service activity focuses on integrated waste processing training activities with Maggot (Black Soldier Fly). The results of this activity, apart from aiming to ensure that organic waste can be managed well, can also develop the results of maggot cultivation into economically valuable products. This activity is carried out using the ABCD method by utilizing the assets owned by the Islamic boarding school. The activity was carried out in the form of simple training on Maggot cultivation. From the results of this training, students and the community around the Islamic boarding school understand the basics of maggot cultivation in integrated waste processing through a simple practicum in integrated organic waste processing with maggots.